A model for evaluating the potential impact of integrating ERP systems with BI systems on organisational performance: an empirical study of the semiconductor industry. (1st January 2014) - Hou, Chung-Kuang
There is currently a trend towards the integration of Business Intelligence (BI) systems with existing Enterprise Resource Planning (ERP) systems in order to improve organisational decision-making capabilities. Although much attention has been paid to the decision-making benefits of integrated systems, limited research has examined the business value of BI systems. Therefore, the main purpose of this study is to examine the impact of integrated ERP and BI (hereafter ERPBI) systems on organisational performance. This study develops a multidimensional measurement for assessing organisational performance. Data collected from 139 companies in the Taiwan's semiconductor industry were tested using partial least squares approach. Our results suggest that ERPBI system usage in organisations results in significant and sustained organisational performance gains. The theoretical implication of the work is the development of multidimensional measurement scales for assessing the impact of ERPBI system usage on organisational performance, based on the balanced scorecard approach.